What Encourages Users to Go Premium? An Analysis of Value, Price Perception, and Brand Experience on Spotify - Seta, Meiyin Frendita Mutiara; Fakhri, Erie Awalil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The use of digital music streaming services continues to increase along with the growth in the number of internet users, yet the conversion rate from free to paid users remains relatively low. The objective of this research is to identify the effects of perceived value, perceived price, and brand experience on the intention of Spotify users to purchase Spotify Premium. This quantitative explanatory research elucidates and proves the relationship between its dependent and independent variables. Using non-probability sampling method and purposive sampling technique, 160 users of free Spotify were selected as the respondents. The data was harvested via online questionnaires and was analyzed using multiple linear regression in SPSS ver. 25. This study finds that the three variables, which are perceived value, perceived price, and brand experience, have positive and significant impacts on the intention to purchase Spotify Premium.